Quality Architecture for Resource Allocation in Cloud Computing - HOUNGUE, Yénukunmè Pélagie Elyse; SAGBO, romaric (My University, 2012)
Quality features are important to be taken into account while allocating resource in Cloud Computing, since it allows to provide to the users or customers, high Quality of Service (QoS) with best response time as example and respects the Service Level Agreement (SLA) established. Indeed, it is not easy to handle eﬃciently resource allocation processes in Cloud, since, the applications deployed on Cloud present non-uniform usage patterns, and the cloud allocation architecture needs to provide diﬀerent scenarios of resource allocation to satisfy the demands and provide quality. In order to provide the measurement of quality indexes, the Cloud resource allocation architecture needs to be proactive and reactive. The goal of this paper is to propose a resource allocation’ architecture for Cloud Computing that provides the measurement of quality indicators identiﬁed between the Key Performance Indicators (KPI) deﬁned by the Cloud Services Measurement Initiative Consortium (CSMIC). Our architecture proposes diﬀerent resource allocation policies: predictive and reactive. The allocation decisions are taken in this architecture, according to the SLA. Finally, the preliminary experimental results show that our proposed architecture can improve quality in Cloud.
Keywords: Cloud Computing; Resource Allocation; Quality Architecture; Quality of Service.